Scalable Synthesis of Photoluminescent Single‐Chain Nanoparticles by Electrostatic‐Mediated Intramolecular Crosslinking. Issue 27 (9th May 2022) - Shao, Yue; Wang, Yong‐Lei; Tang, Zian; Wen, Zhendong; Chang, Chiawei; Wang, Chunyu; Sun, Dayin; Ye, Yilan; Qiu, Dong; Ke, Yubin; Liu, Feng; Yang, Zhenzhong
Abstract: We report the large‐scale synthesis of photoluminescent single‐chain nanoparticles (SCNPs) by electrostatic‐mediated intramolecular crosslinking in a concentrated solution of 40 mg mL −1 by continuous addition of the free radical initiator. Poly(vinyl benzyl chloride) was charged by quaternization with vinyl‐imidazolium for the intramolecular crosslinking by using 2, 2‐dimethoxy‐2‐phenylacetophenone (DMAP) as the radical initiator. Under the electrostatic repulsion thus interchain isolation, the intrachain crosslinking experiences the transition from coil through pearl‐necklace to globular state. The SCNPs demonstrate strong photoluminescence in the visible range when the non‐emissive units are confined thereby. Composition and microstructure of the SCNPs are tunable. The photoluminescent tadpole‐like Janus SCNP can be used to selectively illuminate interfacial membranes while stabilizing the emulsions. Abstract : Fluorophore‐free single‐chain nanoparticles (SCNPs) and Janus derivatives were synthesized on large scale by electrostatic‐mediated intramolecular crosslinking, providing a powerful tool to selectively illuminate interfaces.